Impact of supplementation of lukewarm water during winter on productive performance of dairy cows (Indian Journal of Animal Production and Management, 2024)
The present study was carried out to find the effect of supplementation of lukewarm water during winter  season on physiological parameters and production of Sahiwal cows. The present study was carried out  with twelve healthy, lactating Sahiwal cows maintained at DDD farm within the premises of LFC of DUVASU,  Mathura. These experimental cows were quasi randomly divided into two groups consisting six animals  in each. All the cows were kept in conventional (tail-to-tail) system of housing for whole day. Cows of one  group i.e. control were offered drinking water stored in water trough located in a corner of the shed at  ambient temperature, whereas, the cows of supplemented group were offered lukewarm water at 25°C  which was prepared by mixing of partial amount of warm water in cold water. Cows of both the groups  were offered weighed amount of ad lib water thrice a day (early morning, afternoon and late evening) in  graduated buckets individually. They were also provided weighed amount of ad lib feed. The production  profile of control and treatment group were studied during the course of experiment and compared to  observe the impact of supplementation of lukewarm water during winter season. A significant difference for  total solid % (p
Keywords: Lukewarm water; Lactating Sahiwal; Mathura; Productive attributes